The Effects of Inventory Control on Construction Companies: A Case Study of Kavuma Investments Limited. - Atwongyeire, Pleasure (Kabale University, 2023)
The study was about establishing the effects of inventory control on construction companies in Uganda, a case study of Kavuma Investments Ltd. Chapter one provided the necessary background, statement of the problem, purpose of the study, objectives of the study, research questions, significance of the study area and scope of the study. Chapter two covered a written discussion of related literature search. It was as per the study and reflected the objectives of the research about the effects of inventory control on construction companies in Uganda, a case study of Kavuma Investments Ltd. While reviewing, the research mainly focused on approaches to inventory control, inventory costs incurred in the procurement process and the relationship between approaches of inventory control and the performance of Kavuma Investments Ltd. Chapter three dealt with the methods and tools the researcher used in data collection and analysis. It described the research design that was used by the researcher, data sources and collection tools, processing, analysis and the challenges that the researcher faced. Chapter four focused on the analysis and report of the results of the study. The main issues covered are demographics of the respondents and data presentation in terms of tables and charts to address the objectives of the study. Chapter five provided the discussion of the findings from chapter four, and it also gives the conclusions and recommendations of the study based on the objective of the study.